Food security dynamics in Oman: VECM approach - Devesh, Sonal; M. Asrul Affendi, Abdullah (2020)
The paper examines the determinants of food security in Oman during the period 1980-2019. It investigates the influence of population growth rate and GDP per capita on food security. Cointegration and vector error correction model (VECM) approach are used to identify the long term and short term relationship of food security determinants. The results confirm the existence of a long run relationship among the determinants of food security. Further this linkage indicates that food security in Oman is positively influenced by the population growth rate and GDP/capita(current). The error correction term suggests that 51.7 percent of the total disequilibrium in food security was being adjusted every year which is justifiable for an oil producing country.